Brain banking - Huitinga, Ingeborg; Webster, Maree J. (Handbook of clinical neurology ;, 2018)
"Brain Banking, Volume 150, serves as the only book on the market offering comprehensive coverage of the functional realities of brain banking. It focuses on brain donor recruitment strategies, brain bank networks, ethical issues, brain dissection/tissue processing/tissue dissemination, neuropathological diagnosis, brain donor data, and techniques in brain tissue analysis. In accordance with massive initiatives, such as BRAIN and the EU Human Brain Project, abnormalities and potential therapeutic targets of neurological and psychiatric disorders need to be validated in human brain tissue, thus requiring substantial numbers of well characterized human brains of high tissue quality with neurological and psychiatric diseases"--Publisher's description